Gymnosiphon philippinensis, a new species of Burmanniaceae from Cebu, Philippines - Pelser, Pieter B.; Salares, Val B.; Barcelona, Julie F. (Phytotaxa, 2019)
Gymnosiphon philippinensis is described as a new species of Burmanniaceae from forest over limestone in southern Cebu (Philippines). Among Malesian Gymnosiphon, it is most similar to G. papuanus and G. pauciflorus in having flowers with stamens that are attached in the middle of the floral tube and having outer tepals with entire margins, but these tepals are longer in absolute and relative lengths than those of the aforementioned species. Gymnosiphon philippinensis is the first species of Gymnosiphon reported from the Philippines.